ANALISIS LAJU KOROSI PADA BAJA KARBON DENGAN MENGGUNAKAN AIR LAUT DAN H2SO4 - Kevin Jones Pattireuw; Fentje Abdul Rauf; Romels Cresano Apelles Lumintang (JURNAL POROS TEKNIK MESIN UNSRAT, 2013)
In this study, the materials used as reference are carbon steel and the copper alloy. Corrosion process is done by soaking the material in the test environment and H2SO4 solution of sea water that has collected in a glass aquarium in order to circulate properly with the aid of a pump. The length of immersion performed for 1 hour 3 times as much as 3 hours of immersion and immersion for 3 times. The purpose this study is to determine the corrosion that occurs in the material of carbon steel and copper alloys. Weight loss due to corrosion is closely related to time, in other words increasing immersion time, the greater the weight loss that occurs. The rate of corrosion test results conducted with a time of 1 hour, the average value obtained for the specimen I in of carbon steel and copper alloys in seawater solution is 0,105 mils / year and 0 mils / year. While in the sulfuric acid solution is 0,162 mils / year and 0,028 mils / year. And the rate of corrosion test results conducted by 3 hours, the average value obtained for the specimen I in of carbon steel and copper alloys in sea water solution and sulfuric acid is 1,350 mils / year and 0,015 mils / year. While in the sulfuric acid solution is 1,400 mils / year and 1,306 mils / year.